قرينة البراءة الاصلية وأثرها في مرحلة التحقيق - دراسة مقارنة بين الفقه الاسلامي والتشريع الجزائري - جابو, شيماء; حرابي, رميساء (University of Eloued-جامعة الوادي, 2022)
الملخص: يدرس البحث قرينة البراءة و يركز على اثرها في مرحلة التحقيق في الفقه الاسلامي و التشريع الجزائري ، و بهدف البحث الى التعريف بهذا المبدأ و بيان اساسه الشرعي و القانوني ، كما يهدف الى بيان اثر هذا المبدأ على المتهم في مرحلة التحقيق ، و من اهم النتائج التي توصل اليها البحث ان الفقه الاسلامي و التشريع الجزائري كفلا مبدأ البراءة الاصلية و عداه من حقوق المتهم ، و اهم اثار هذا المبدأ على المتهم هو معاملته على انه بريء حتى تثبت الادانة ، و كذلك تفسير كل شك في الادلة لصالح المتهم . Abstract The research studies the presumption of original innocence and focuses on its impact on the stage of investigation in Islamic jurisprudence and Algerian legislation , The research aims to define this principle and clarify its legal basis. It also aims to show the impact of this principle on the accused during the investigation stage. among the most important findings of the research is that Islamic jurisprudence and Algerian legislation guaranteed the principle of original innocence and considered it among the rights of the accuse , the most important effects of this principle on the accused is the treatment of him as innocent proven guilty , as well as the interpretation of any doubt about the avidence in favor of the accused .
مذكرة ماستر
Keywords: قرينة البراءة ، مرحلة التحقيق ، المتهم; presumption of innocence ; investigation stage ; Accused